Philosophy, Education, and Values Religious in Culture Pegon Jaranan Dance - Andry Ferdian; Rusman Rusman; Asrori Asrori (Nazhruna: Jurnal Pendidikan Islam, 2022)
The purpose of this study is to describe the philosophical, educational, and religious values ​​of the Jaranan Pegon art and culture. Because many people have not been able to catch this, and including the cultural arts players themselves, so the performances are an only spectacle, without making it a guide. Meanwhile, nowadays, the influence of globalization, and technological advances, is increasingly threatening the next generation of the nation, the erosion of the original culture of Indonesia, and also the eastern character that emphasizes etiquette and morals, as well as good manners. What is later feared that Indonesia will lose the next generation of the nation as expected. Method Objectives This research uses qualitative research methods (by observation, in-depth interviews, and documentation) to explore the philosophical, educational, and religious values ​​that exist in the art and culture of Jaranan Pegon. The results of the study can be seen that the art of jaranan culture has the potential to be a means of education, learning facilities and means of da'wah to the actors of the jaranan arts themselves and the community. This potential will grow if it is supported by the active role of community leaders and scholars.